Roman Crete and the Letter to Titus - Wieland, George M. (New Testament studies, 2009)
Crete is rarely taken seriously as a plausible actual destination for the NT letter to Titus. Investigation of Roman Crete, however, yields intriguing points of contact with puzzling features of the letter. Patterns of social organisation on the island correlate closely to the structure of behavioural instruction in Titus 2.1–10, suggesting that it might have been shaped specifically to that environment. Unusual elements of the major theological statements in Titus correspond to aspects of Cretan religion in ways that could represent intentional engagement. There are implications for identifying the letter's provenance and interpreting it as a missionary document.